Synthesis and antimicrobial activity of 3,5-R-4-(3-(5-nitrofuran-2-yl)-allylidenamino)-1-R1-4H-1,2,4-triazole halides derivatives - T. S. Brytanova; A. S. Gotsulya; O. I. Panasenko; Ye. G. Knysh; N. S. Fedyunina (Zaporožskij Medicinskij Žurnal)
Aim. A number of new 3,5-R-4-(3-(5-nitrofuran-2-yl)allylidenami-no)-1-R1-4H-1,2,4-triazole halides have been synthesized, the structure of synthesized compounds has been proved by modern physical-chemical methods.